The syntax of anaphora - Safir, Kenneth J.; Oxford eBooks (New York ; Oxford : Oxford University Press, 2004)
In this work, Ken Safir develops a comprehensive theory on the role of anaphora in syntax.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Anaphora (Linguistics); Grammar, Comparative and general -- Syntax; Electronic books